Observation of a mesospheric front in a thermal-doppler duct over King George Island, Antarctica - Bageston, JV; Wrasse, CM; Batista, PP; Hibbins, Robert; Fritts, DC; Gobbi, D; Andrioli, VF (Atmospheric Chemistry and Physics, 2015)
A mesospheric front was observed with an all-sky airglow imager on the night of 9–10 July 2007 at Ferraz Station (62° S, 58° W), located on King George island on the Antarctic Peninsula. The observed wave propagated from southwest to northeast with a well defined wave front and a series of crests behind the main front. The wave parameters were obtained via a 2-D Fourier transform of the imager data providing a horizontal wavelength of 33 km, an observed period of 6 min, and a horizontal phase speed of 92 m s−1. Simultaneous mesospheric winds were measured with a medium frequency (MF) radar at Rothera Station (68° S, 68° W) and temperature profiles were obtained from the SABER instrument on the TIMED satellite. These wind and temperature profiles were used to estimate the propagation environment of the wave event. A wavelet technique was applied to the wind in the plane of wave propagation at the OH emission height spanning three days centered on the front event to define the dominant periodicities. Results revealed a dominance of near-inertial periods, and semi-diurnal and terdiurnal tides suggesting that the ducting structure enabling mesospheric front propagation occurred on large spatial scales. The observed tidal motions were used to reconstruct the winds employing a least-squares method, which were then compared to the observed ducting environment. Results suggest an important contribution of large-scale winds to the ducting structure, but with buoyancy frequency variations in the vertical also expected to be important. These results allow us to conclude that the wave front event was supported by a duct including contributions from both winds and temperature. © Author(s) 2011. This work is distributed under the Creative Commons Attribution 3.0 License.